Evaluating the Resilience Level and Its Association to Psychological Parameters Among Nursing Students in Universiti Sains Malaysia - Logeswary K Vesupathy; Jamilah Al-Muhammady Mohammad; Norhasmah Md Zain; Anisa Ahmad (Education in Medicine Journal, 2026)
This study evaluated the resilience level among nursing students at Universiti Sains Malaysia (USM) and its association with psychological parameters. A total of 240 students from Year 1 to Year 4 were recruited through purposive sampling, and 186 responded (77.5% response rate). Data were collected via a Google Forms questionnaire distributed through WhatsApp, includingdemographic information, the Connor-Davidson Resiliency Scale (CD-RISC 25), and the General Health Questionnaire (GHQ-28). Resilience levels were categorised as significant or non-significant based on CD-RISC 25 scores. The highest domain mean was for managing negative emotions or stress (mean = 3.621, SD = 0.68). Statistical analyses showed that gender and educational level were significantly associated with resilience (p < 0.001). Age and years of study were also linked to resilience levels. Multiple linear regression revealed significant associations between resilience and psychological parameters, specifically somatic symptoms, anxiety, and insomnia. The findings suggest that USM nursing students demonstrated resilience, which was associated with various psychological factors. Therefore, interventions to enhance resilience are essential to support students in managing academic and clinical psychological stress.